Exploring the willingness to pay for a quality-adjusted life-year in the state of Penang, Malaysia - Shafie AA; Lim YW; Chua GN; Hassali MA (Dove Medical Press, 2014)
Asrul Akmal Shafie, Yen Wei Lim, Gin Nie Chua, Mohammed Azmi Ahmad Hassali Discipline of Social and Administrative Pharmacy, School of Pharmaceutical Sciences, Universiti Sains, Penang, Malaysia Introduction: The incremental cost-effectiveness ratio (ICER) is typically compared with a reference value to support the cost-effectiveness of a decision. One method for estimating this value is to estimate the willingness-to-pay (WTP) for a quality-adjusted life-year (QALY). This study was conducted to explore the WTP for a QALY in the Malaysian population. Methods: A cross-sectional, contingent valuation study was conducted in Penang, Malaysia. Respondents were selected from randomly chosen geographical grids of Penang. Respondents’ sociodemographic information, qualities of life, and WTP for one additional QALY were collected using predesigned questionnaires in face-to-face interviews. WTP values were elicited using a double-bound dichotomous choice via a bidding game approach. The Heckman selection model was applied to the analysis of the mean WTP/QALY values, where the “protest zero” values, which may contribute to selection bias, were excluded. Results: The mean value of WTP for an additional QALY gained was estimated to be MYR (Malaysian Ringgit) 29,080 (~USD 9,000). Key factors that affected the WTP include ethnicity and estimated monthly household income. Conclusion: The study findings suggested that the cost-effectiveness threshold value as studied in Penang, Malaysia was estimated to be MYR 29,080. Keywords: WTP, QALY, cost-effectiveness threshold, contingent valuation method, Malaysia